Effects of a lifestyle intervention on the biomarkers of oxidative stress in non-communicable diseases: A systematic review - Husain, Sarah; Hillmann, Katharina; Hengst, Karin; Englert, Heike (Frontiers in Aging, 2023)
Abstract: Oxidative stress plays a critical role in the pathogenesis of chronic diseases. Therefore, improvement of oxidative stress status through lifestyle intervention can play a vital role in preventing and treating chronic diseases. The aim of this systematic review is to provide an overview of articles published in the last decade examining the association between lifestyle intervention and oxidative stress biomarkers in the context of non-communicable diseases. The electronic databases PubMed and Web of Science were searched for relevant studies, following the PRISMA (Preferred Reporting of Systematic Reviews and Meta Analyses) guidelines. This systematic review was focused on the four important oxidative stress biomarkers; glutathione (GSH), superoxide dismutase (SOD), catalase, and malondialdehyde. 671 articles were identified, of which nine met the inclusion criteria. A trend emerged, showing that lifestyle modifications which focuses on diet and physical activities can improve oxidative stress in the form of an increase in SOD and CAT levels and a decrease in MDA levels in participants with non-communicable diseases (NCDs),. GSH levels were not affected. However, the results are difficult to compare because of the heterogeneity of methods of the biomarkers studied. Our review suggests that oxidative stress can be improved by Lifestyle modifications and may be an effective treatment for the prevention and management of non-communicable diseases, this review also elucidated the importance of analysing multiple oxidative stress biomarkers as a tool to evaluate the oxidative stress, it further stressed the need to conduct long- term standardized lifestyle intervention studies focused on improving oxidative stress levels to combat chronic diseases. Keywords: Oxidative Stress; Lifestyle intervention; lifestyle diseases; antioxidants; non-communicable diseases; prevention; antioxidants; ageing; immunity.